Despairing Like the Scandinavians – the Romantic Aesthetics of Karin Boye and Maria Pawlikowska-Jasnorzewska - Skoczyńska, Maria (Poznańskie Studia Slawistyczne, 2023)
In Romantic aesthetics there is an interpretive category of the poetry of the cultures of the North – including the Scandinavians, who were familiar with the “poetry of the night and the graves” – which expressed ferocity, gloom, harshness, melancholy, internal tensions. Maria Janion repeatedly referred to the parallel between Polish and Scandinavian literatures, writing: “It is good that there are despairing Scandinavians in the world.” This article will focus precisely on the aesthetics of Romantic “existential despair” and “gender despair” in the context of the poetry created by a Swedish woman, Karin Boye, and a Polish woman, Maria Pawlikowska-Jasnorzewska, with particular emphasis on their last poems, written in the late 1920s and early 1930s. And although they do not create in the Romantic era – they implement Romantic aesthetics in their poetic program.